2022
DOI: 10.1128/jb.00606-21
|View full text |Cite
|
Sign up to set email alerts
|

The Consistent Tick-Vertebrate Infectious Cycle of the Lyme Disease Spirochete Enables Borrelia burgdorferi To Control Protein Expression by Monitoring Its Physiological Status

Abstract: The Lyme disease spirochete, Borrelia burgdorferi , persists in nature by alternatingly cycling between ticks and vertebrates. During each stage of the infectious cycle, B. burgdorferi produces surface proteins that are necessary for interactions with the tick or vertebrate tissues it encounters while also repressing the synthesis of unnecessary proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 186 publications
(197 reference statements)
0
17
0
Order By: Relevance
“…Genes encoding Elps are located on 32-kilobase circular plasmids (i.e. cp32 genetic elements) and are expressed during the mammalian phase of infection, suggesting a potential role in host interaction, which is further supported by the identification of laminin as a binding partner for ErpX/ElpX (35)(36)(37)(38)(39). We showed that ElpB and ElpQ bound with high affinity to the CP proteases C1r and C1s and were selective for the activated forms of each protease (31).…”
Section: Introductionmentioning
confidence: 71%
“…Genes encoding Elps are located on 32-kilobase circular plasmids (i.e. cp32 genetic elements) and are expressed during the mammalian phase of infection, suggesting a potential role in host interaction, which is further supported by the identification of laminin as a binding partner for ErpX/ElpX (35)(36)(37)(38)(39). We showed that ElpB and ElpQ bound with high affinity to the CP proteases C1r and C1s and were selective for the activated forms of each protease (31).…”
Section: Introductionmentioning
confidence: 71%
“…In this bacterium, the operon dnaX-ebfC is regulated by a promoter located upstream of dnaX [ 30 ]. In addition, ebfC can also be expressed by a promoter located in the dnaX structural sequence, as determined by RT-PCR and GFP-transcriptional fusions [ 30 , 38 ]. In addition, DnaA, one of the main proteins of chromosomal replication, has been suggested to be involved in the regulation of expression of the dnaX - ebfC operon in B. burgdorferi, as discussed by Stevenson et al [ 38 ].…”
Section: Operon Structure and Expressionmentioning
confidence: 99%
“…Cp32s, one of these elements, is circular and presents characteristics of a bacteriophage genome [ 57 ]. Among other traits, Cp32s contain genes that encode a polymorphic family of surface lipoproteins, the Erp proteins, involved in pathogenesis by promoting binding to plasminogen, laminin, and complement factor H, thus conferring adhesion to host tissues and inhibiting complement activation [ 38 ]. EbfC was found to regulate the transcription of erp operons by binding to operator sequences in the promoter region of erp genes.…”
Section: Ebfc/ybab Has Important Biological Functionsmentioning
confidence: 99%
See 2 more Smart Citations